A Two-Dimensional Semantics for Epistemic Modals - Dan Quattrone (Philosophia Scientiæ, 2012)
Not everyone knows that water is H2O. Suppose Alice is one of those people. Alice says: "For all I know, water might not be H2O." Intuitively it seems like Alice has spoken truly. That is, it seems like it is epistemically possible (for Alice) that water is not H2O. However, conventional accounts of modality in linguistics and philosophy of language predict that any metaphysically impossible statement will also be epistemically impossible (for anyone). And there are plausible arguments, from Kripke and others, that purport to show that it is metaphysically impossible for water to be anything other than H2O. So according to the standard accounts of modality, Alice has in fact said something false.